PRINSIP-PRINSIP ISLAM TENTANG MANAJEMEN DAN PRAKTIK PENDIDIKAN DI LEMBAGA PENDIDIKAN ISLAM - Aini Safitri; Hendra Sh (Program Studi Manajemen Pendidikan Islam, 2022)
Abstract Islamic principles of management and educational practices in Islamic educational institutions are very important to be studied to be implemented in real terms. With this study, we will know the Islamic principles of management, and educational practices in Islamic educational institutions. The purpose of writing this article is to find out and explain how Islamic principles of management, and how educational practices in Islamic educational institutions. The results of the analysis and discussion found: Islamic principles of management are seen from four activities, namely; planning in Islam, organizing Islamic educational resources, providing motivation and leadership in Islamic education, and supervision in Islam. Then, to achieve a perfect living system as the characteristics of Islamic education and the objectives of national education, the three educational pathways in the form of informal, formal, and non-formal education are not only complementary or complementary but must be synchronized, should not run independently and must be an integral unit to prepare the nation's generation to have a character that covers all aspects of life, both in the form of physical, mental, faith and morals, emotional, aesthetic and social to achieve success in life in the world and in the hereafter, as well as harmony in the implementation of education as a perfect living system and efforts to organize national education so that our education does not become redundant.